2015
DOI: 10.3748/wjg.v21.i4.1315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of incidental or unsuspected gallbladder cancers diagnosed during or after cholecystectomy: A systematic review and meta-analysis

Abstract: A large proportion of incidental GB cancers were T2 and T3 lesions. Revisional surgery for radical cholecystectomy is warranted in T2 and more advanced cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 54 publications
5
77
0
Order By: Relevance
“…Hayes and Muldoon [20] systematically surveyed 2,522 cholecystectomy records from an Irish population and reported similar frequencies of dysplasia (1.15%) and carcinoma (0.48%). These data are in agreement with a Cochrane review on 26 studies including 2,145 patients with a diagnosis of incidental or unsuspected GbCa during or after cholecystectomy, where cancerous lesions were found in 0.7% (95% CI 0.004 -0.012) [21]. In a small study in an Indian population (310 cases), 27 (8.7%) had acute cholecystitis, 280 (91.2%) chronic cholecystitis, 2 out of 290 cases with cholelithiasis (0.7%) were found to have coexistent histologically proven GbCa [22].…”
Section: Environmental Risk Factors For Gallbladder Cancersupporting
confidence: 91%
“…Hayes and Muldoon [20] systematically surveyed 2,522 cholecystectomy records from an Irish population and reported similar frequencies of dysplasia (1.15%) and carcinoma (0.48%). These data are in agreement with a Cochrane review on 26 studies including 2,145 patients with a diagnosis of incidental or unsuspected GbCa during or after cholecystectomy, where cancerous lesions were found in 0.7% (95% CI 0.004 -0.012) [21]. In a small study in an Indian population (310 cases), 27 (8.7%) had acute cholecystitis, 280 (91.2%) chronic cholecystitis, 2 out of 290 cases with cholelithiasis (0.7%) were found to have coexistent histologically proven GbCa [22].…”
Section: Environmental Risk Factors For Gallbladder Cancersupporting
confidence: 91%
“…However, 47% of these tumors are incidentally diagnosed following the examination of a cholecystectomy specimen (5). The incidence of gallbladder cancer in cholecystectomy specimens ranges from 0.2% to 3% (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…They also revealed that in most studies proper number of lymph nodes were either not resected or not sent which is case with our study as well. A meta-analysis involving 986 articles by Choi et al [8] found that most important clinical dilemma with IGBC is decision of second stage surgery both at clinician as well as patient end. Same dilemma is visible in our series where majority of patients refused definitive surgery in spite of thorough counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in oncogenes, tumor suppressor genes, microsatellite instability and methylation of gene promoter areas act in synergy with recurrent or chronic mucosal inflammation to induce cancer although exact cause in not known [30]. Gallstones especially chronic one pose most significant risk although other suspected culprits [31] are advance age, female sex, positive family history, cholelithiasis, obesity (BMI > 30), parasitic infestations, chronic bacterial cholangitis especially by Salmonella and Helicobacter [32], porcelain gallbladder, large polyps >10 mm, heavy metals exposure and abnormal pancreaticobiliary duct junction [33] Clinical features are ominous but those harboring clue include persistent right upper quadrant pain, jaundice, nausea and weight loss [8]. Biochemical investigations are nonspecific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation